The Effects of Non‐Pharmacological Interventions on Depression Among Community‐Dwelling Individuals With Spinal Cord Injury: A Systematic Review and Network Meta‐Analysis - Yangfan Hu; Xinyi Guo; Mengmeng Jia; Yingmin Wang; Lirong Zhong; Kun Li (Journal of Clinical Nursing, 2026)
ABSTRACT Aims and Objectives To compare and rank the effectiveness of various non‐pharmacological interventions on depression for community‐dwelling individuals with spinal cord injury (SCI). Background Depression is a significant and persistent mental health problem among community‐dwelling individuals with SCI. There is increasing evidence that non‐pharmacological interventions are safe and effective for alleviating depression. However, the efficacy and comparative effectiveness of various non‐pharmacological interventions for community‐dwelling individuals with SCI remain unclear. Design Systematic review and network meta‐analysis (NMA) according to PRISMA‐NMA guidance. Methods We included randomized controlled trials (RCTs) of community‐dwelling individuals with SCI comparing non‐pharmacological interventions versus usual care/waiting list and reporting depressive symptoms using validated scales. China National Knowledge Infrastructure, Wanfang Data, Chinese Biomedical Literature Database, China Science and Technology Journal Database, the Cochrane Library, PubMed, Web of Science, Embase, ProQuest and Scopus were systematically retrieved. Pairwise meta‐analyses were performed using Review Manager 5.4.1, and the network meta‐analysis was conducted using Stata 15.1. Results Thirty‐two RCTs involving 2200 participants were identified from database inception to May 2026. Compared with the control group, combination therapy (SMD = −0.86, 95% CI: −1.46 to −0.27), exercise therapy (SMD = −0.66, 95% CI: −1.16 to −0.15), psychological interventions (SMD = −0.41, 95% CI: −0.70 to −0.13) and self‐management education (SMD = −0.33, 95% CI: −0.61 to −0.05) showed statistically significant effects, whereas vocational rehabilitation was not (SMD = −0.03, 95% CI: −1.00 to 0.95). Combination therapy had the highest SUCRA (89.1%, mean rank = 1.5), followed by exercise therapy (76.9%, mean rank = 2.2), psychological interventions (55.5%, mean rank = 3.2), self‐management education (44.0%, mean rank = 3.8) and vocational rehabilitation (24.7%, mean rank = 4.8). Conclusion Combination therapy had the highest ranking probability. However, all comparisons were rated as very low certainty according to CINeMA. The findings should be interpreted with caution. Relevance to Clinical Practice Community nurses may consider integrating exercise, self‐management education and brief psychological support into individualized depression management for individuals with SCI. Support should be tailored according to depressive symptom severity, functional status, secondary complications, patient preferences, safety considerations and available community resources. Nurse‐led or nurse‐coordinated care may include depressive symptom screening, exercise planning, self‐management coaching, motivational interviewing, scheduled follow‐up and referral to mental health professionals when indicated. Trial Registration PROSPERO: CRD42022342155